The EU Member States and the Crisis in Ukraine: Towards an Eclectic Explanation - André Härtel (Romanian Journal of European Affairs, 2019)
The decision of the European Union (EU) to adopt and extend far-reaching sanctions against the Russian Federation came as surprise to many critics of the Common Foreign and Security Policy (CFSP). Especially in light of the history of EU-Russian relations and the deep divisions between member states when it comes to Russia-policy the Ukraine Crisis has become a turning point. This article tries to trace the roots of the EU’s response to the crisis by looking at the level of the member states. In analysing three «most unlikely» cases (Germany, Italy, Austria) one-dimensional IR explanations are rejected. One needs to look for an eclectic approach instead. I argue here that Germany’s surprising leadership role during the crisis can be understood by personal, learning-based and normative factors. Italy and Austria did not change national Russia-policy and their «critical consent» to EU-sanctions is based on a yet firm but increasingly more fragile commitment to the European project and order. Based on the findings the article concludes with a skeptical note on both the sustainability of the EU’s current Russia-policy and European foreign policy development as such.